From SGML to XML with TEI: Automated Conversion of a Corpus of Polish from P3 to P4 Format - Ogrodniczuk, Maciej (Investigationes Linguisticae, 2004)
The article presents experiences gathered in the process of migration of an SGML corpus encoded in TEI P3 format to XML-enabled TEI P4.